2001
DOI: 10.2165/00124363-200102000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The bioequivalence of standard sumatriptan tablets and two encapsulated forms of sumatriptan

Abstract: The bioequivalence of encapsulated vs standard (commercial) sumatriptan was assessed before comparative eletriptan-sumatriptan efficacy studies in the acute treatment of migraine were conducted. Commercially acquired sumatriptan was encapsulated to ensure the double-blind nature of these studies.The pharmacokinetics of three single oral doses of sumatriptan 100 mg -the standard tablet, an encapsulated tablet, and a stressed encapsulated tablet -were compared in an open, randomized, three-way crossover study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The encapsulated sumatriptan was demonstrated to be equivalent to the commercial tablet based on in vitro dissolution conducted in deionized water (data on file). In vivo pharmacokinetic comparison of encapsulated sumatriptan and sumatriptan standard tablets performed by Milton et al (11) showed equivalence of encapsulated sumatriptan. Patients treated three migraine attacks during a study period of 3 months per patient.…”
Section: Methodsmentioning
confidence: 97%
“…The encapsulated sumatriptan was demonstrated to be equivalent to the commercial tablet based on in vitro dissolution conducted in deionized water (data on file). In vivo pharmacokinetic comparison of encapsulated sumatriptan and sumatriptan standard tablets performed by Milton et al (11) showed equivalence of encapsulated sumatriptan. Patients treated three migraine attacks during a study period of 3 months per patient.…”
Section: Methodsmentioning
confidence: 97%
“…Each study used a randomized, placebo‐controlled, parallel‐group, double‐dummy design in which the double‐blind was maintained by matching plain white film‐coated tablets of eletriptan to placebo tablets, and gelatin capsules containing sumatriptan to matching placebo capsules. The blinded sumatriptan was demonstrated to be both bioequivalent and clinically equivalent to the commercial tablet based on five categories of data: (i) an in vitro dissolution study conducted in deionized water (Milton et al , 2001), (ii) an in vivo gamma scintigraphy study showing dissolution (Wilding et al. , 2003), (iii) bioequivalence studies meeting standard regulatory criteria for equivalent AUC and C max values (Milton et al , 2001); (iv) a pooled analysis of three bioequivalence studies confirming early bioequivalence at the 2‐h time point (AUC 0−2h ; data on file, Pfizer Inc.); and (v) a post hoc comparison of the therapeutic gain for headache response at 2 h. In the current pooled analysis, encapsulated sumatriptan showed a 2‐h headache response (and therapeutic gain) of 57.5% (31.2%), which is equivalent to what has been reported across all available placebo‐controlled studies of the 100‐mg dose of sumatriptan, 59% (29%) (Ferrari et al.…”
Section: Methodsmentioning
confidence: 99%
“…[1] In fact, no relationship of AUC 0-2 with 'therapeutic effect' has been established for sumatriptan. The critique in the above letter is based on a highly selective review of available data and an unusual interpretation of bioequivalence.…”
Section: Replymentioning
confidence: 99%
“…
The bioequivalence of standard sumatriptan tablets and two encapsulated forms of sumatriptan Milton et al reported a study claiming to demonstrate the bioequivalence of sumatriptan tablet versus two variations of encapsulated sumatriptan [1]. Pfizer conducted this bioequivalence study to validate their decision to use encapsulated sumatriptan while not similarly encumbering their own product, eletriptan, in three Pfizer-sponsored comparator trials.
…”
mentioning
confidence: 99%